Inhibitory Effects of Eight Green Tea Catechins on Cytochrome P450 1A2, 2C9, 2D6, and 3A4 Activities - Takashi Satoh; Haruka Fujisawa; Ami Nakamura; Natsuko Takahashi; Kazuhiro Watanabe (Frontiers Media S.A., 2016)
PURPOSE: Green tea is a traditional beverage that has been enjoyed by the Japanese to this day. Recently, there has been an increase in the consumption of green tea beverage having high concentrations of catechins, such as (-)-epigallocatechin-3-O-gallate (EGCG). Many people tend to ingest large amounts of catechins through the frequent consumption of green tea beverage, and this dietary habit may lead to unwanted interactions between the catechins in green tea and medicinal drug. METHODS: The inhibitory effects of eight green tea catechins on drug metabolizing enzymes, cytochrome P450 (CYP) 1A2, 2C9, 2D6, and 3A4, were investigated in human liver microsomes. Incubation was initiated by the addition of cocktail probe drugs that served as specific substrates for each CYP, and the resulting metabolites were analyzed by LC-MS. RESULTS: From a comparison of the fifty percent inhibitory concentration (IC50) values of the eight green tea catechins, it was found that non-gallated catechins did not inhibit CYPs, whereas gallated catechins inhibited all CYPs except CYP2D6. Among them, CYP2C9 was most strongly inhibited by (-)-catechin-3-O-gallate (CG) (7.60 µM), and CYP1A2 was most strongly inhibited by EGCG (8.93 µM). Catechin gallate exhibited non-competitive inhibition of CYP2C9, and its Ki value was 9.76 ± 0.47µM. The present study is the first to report the inhibitory effect of CG on CYP2C9. In contrast, EGCG showed competitive inhibition of CYP1A2, and its Ki value was 14.3 ± 0.09 µM. CONCLUSION: Previous reports had predicted that plasma EGCG concentration reached 7.4 µM after ingesting green tea having high concentrations of catechins. That concentration of EGCG is equivalent to one-half to one-third of its Ki value for CYP1A2 and CYP3A4 in this study. The ingestion of beverages containing large amounts of green tea catechins together with drugs that are metabolized by CYP1A2, CYP2C9, and CYP3A4 should be avoided.   This article is open to POST-PUBLICATION REVIEW. Registered readers (see "For Readers") may comment by clicking on ABSTRACT on the issue's contents page.